Uncertainty-Aware Few-Shot Image Classification - Zhang, Zhizheng; Lan, Cuiling; Zeng, Wenjun; Chen, Zhibo; Chang, Shih-Fu (to appear in International Joint Conference on Artificial Intelligence (IJCAI), 2021., 2021)
.